The local cell curvature guides pseudopodia towards chemoattractants - Van Haastert, Peter J.M. (HFSP Publishing, 2009)
Many eukaryotic cells use pseudopodia for movement towards chemoattractants. We developed a computer algorithm to identify pseudopodia, and analyzed how pseudopodia of Dictyostelium cells are guided toward cAMP. Surprisingly, the direction of a pseudopod is not actively oriented toward the gradient, but is always perpendicular to the local cell curvature. The gradient induces a bias in the position where the pseudopod emerges: pseudopodia more likely emerge at the side of the cell closer to the gradient where perpendicular pseudopodia are pointed automatically toward the chemoattractant. A mutant lacking the formin dDia2 is not spherical but has many invaginations. Although pseudopodia still emerge at the side closer to the gradient, the surface curvature is so irregular that many pseudopodia are not extended toward cAMP. The results imply that the direction of the pseudopod extension, and therefore also the direction of cell movement, is dominated by two aspects: the position at the cell surface where a pseudopod emerges, and the local curvature of the membrane at that position.